Penggunaan Metode Malcolm Baldrige pada UMKM - M Edhie Hartono; Rabit Pratama; Atika Raid Khorunnisa; Franky Widia Putra; Kusuma Candra Kirana (Ekonomis: Journal of Economics and Business, 2023)
This study aims to analyze the use of Malcolm Baldrige's theory in developing SMEs. This study uses quantitative methods. These results prove that Malcolm Baldrige's sanye theory can be used or can be applied to MSMEs